Financial advice and stock market participation - Dimitris Georgarakos; Roman Inderst (European Central Bank (ECB), 2011)
We introduce professional financial advice in households' choice to hold risky financial assets. Consistent with the predictions from a formal model, we present evidence that households' trust in financial advice only matters when their perceived own financial capability is low. Instead, for households with higher financial capability, only the perception of legal protection in financial markets matters for stock market participation. Our empirical analysis highlights economically significant differences in households' perception of their rights as consumers of financial services, even when their objective circumstances should not be much different.
Keywords: E1; G2; D8; 330; Consumer Protection; Financial Advice; Household finance; Trust